2021
DOI: 10.1108/pr-12-2019-0708
|View full text |Cite
|
Sign up to set email alerts
|

The role of ethical leadership in enhancing exploitative and explorative learning simultaneously: what does it matter if employees view work as central?

Abstract: PurposeThe present study aimed to test the hypothesis that ethical leadership positively contributes to exploitative learning and explorative learning simultaneously and then examine the moderating role of work centrality in the relationships of ethical leadership with exploitative learning and explorative learning.Design/methodology/approachTime-lagged survey data were collected from 257 middle managers and their 257 immediate supervisors in 76 firms in China. Data were analyzed using structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 81 publications
(142 reference statements)
0
20
2
Order By: Relevance
“…Fourth, while we found support for the notion that spiritual leadership is beneficial in the context of workplace hazing, other types of leadership could prove fruitful. Ethical leadership (Abdullah et al , 2019; Ali et al , 2022b; Brown et al , 2005; Usman and Hameed, 2017), transformational leadership (Gui et al , 2020), authentic leadership (Ribeiro et al , 2020; Wang and Xie, 2020) and servant leadership (Liden et al , 2015) can help us develop insights into the role of leadership in reducing or deterring hazing behaviors in hospitality organizations. Studies should also examine whether different negative leadership styles, such as despotic leadership (Albashiti et al , 2021) and narcissistic leadership (Aboramadan et al , 2021), affect workplace hazing in the hospitality context.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, while we found support for the notion that spiritual leadership is beneficial in the context of workplace hazing, other types of leadership could prove fruitful. Ethical leadership (Abdullah et al , 2019; Ali et al , 2022b; Brown et al , 2005; Usman and Hameed, 2017), transformational leadership (Gui et al , 2020), authentic leadership (Ribeiro et al , 2020; Wang and Xie, 2020) and servant leadership (Liden et al , 2015) can help us develop insights into the role of leadership in reducing or deterring hazing behaviors in hospitality organizations. Studies should also examine whether different negative leadership styles, such as despotic leadership (Albashiti et al , 2021) and narcissistic leadership (Aboramadan et al , 2021), affect workplace hazing in the hospitality context.…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, numerous studies found that ethical leadership had positively related to reduced job stress and improved performance quality (Schwepker and Dimitriou, 2021 ), inhibited workplace bullying (Ahmad, 2018 ), increased professional caregivers' wellbeing and patients' perceptions of quality of care (Gillet et al, 2018 ), and promoted employee success through raising psychological empowerment and emotional exhaustion. In the organizational dimension, evidence proved that ethical leadership had a positive effective on the organizational outcomes (Khan et al, 2019 ) and played a critical role in promoting employee loyalty (Fan et al, 2021 ), rising corporate social responsibility, firm reputation, and firm performance (Nguyen et al, 2021 ), enhancing leader–member exchange quality and creative process engagement (Nasser et al, 2021 ), increasing organizational trust and organizational sustainable development (Ilyas et al, 2020 ), enabling innovation through technology (Lin et al, 2020 ), influencing employees' perception of the industrial relations climate (Jha and Singh, 2019 ), determining service employees' engagement in knowledge-hiding behaviors (Abdullah et al, 2019 ), enhancing exploitative and explorative learning simultaneously (Ali et al, 2022 ), deducing purchasers' unethical behavior (Ko et al, 2019 ), and so on.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…When an organization strives for being exploitative, it tends to be more confident and faster, closer and more transparent in its activities. Exploitative suggests less effort for large-scale, above-mean and long-term innovations, which can lead to the deterioration of organizational knowledge (Ali et al , 2021). Exploitative is also related to knowledge for continuous improvement, modification, refinement and development of changes in current products, processes and services (O’Reilly and Tushman, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%